Prevalence and assemblage distribution of Giardia intestinalis in farmed mink, foxes, and raccoon dogs in northern China - Liu, Shuo; Zhang, Miao; Xue, Nian-Yu; Wang, Hai-Tao; Li, Zhong-Yuan; Qin, Ya; Li, Xue-Min; Hou, Qing-Yu; Jiang, Jing; Yang, Xing; Ni, Hong-Bo; Wen, Jian-Xin (Frontiers in Veterinary Science, 2025)
Giardia intestinalis is a widespread protozoan parasite associated with significant health risks in humans and animals. However, there is a lack of epidemiological data regarding this parasite in fur-animals. The present study aimed to investigate the prevalence and assemblage distribution of G. intestinalis in fur-animals in northern China. A total of 871 fecal samples were detected by nested PCR. The results showed an overall infection rate of 1.15%, with the highest rate in Hebei province (2.28%), while no positive cases were observed in Jilin and Heilongjiang provinces. Although no significant differences were found in species group, raccoon dogs (1.72%) were more susceptible to infection than mink (1.40%) and foxes (0.57%). Additionally, the highest infection rate was observed in farms with fewer than 2,000 animals (1.41%), followed by farms with ≥5,000 (0.93%) and those with 2,000–5,000 animals (0.75%). The infection rate was higher in juvenile animals (1.35%) compared to adults (1.08%), and in non-diarrheal animals (1.16%) compared to diarrheal animals (1.08%). Notably, this study is the first to report assemblage A in mink, this finding highlight the potential role of mink as a reservoir for zoonotic transmission. Assemblage D was detected in foxes and raccoon dogs, further suggesting that these animals may serve as potential zoonotic reservoirs. These findings not only complements the epidemiological data of G. intestinalis in fur-animals but also emphasize the importance of monitoring the fur industry to mitigate public health risks.